Influence of Small Change of Porosity on Shock Initiation of an HMX/TATB/Viton Explosive and Ignition and Growth Modeling. Issue 3 (2nd July 2016) - Liu, Yan; Hussain, Tariq; Huang, Fenglei; Duan, Zhuoping
Abstract : All solid explosives in practical use are more or less porous. Although it is known that the change in porosity affects the shock sensitivity of solid explosives, the effect of small changes in porosity on the sensitivity needs to be determined for safe and efficient use of explosive materials. In this study, the influence of a small change in porosity on shock initiation and the subsequent detonation growth process of a plastic-bonded explosive PBXC03, composed of 87% cyclotetramethylene-tetranitramine (HMX), 7% triaminotrinitrobenzene (TATB), and 6% Viton by weight, are investigated by shock to detonation transition experiments. Two explosive formulations of PBXC03 having the same initial grain sizes pressed to 98 and 99% of theoretical mass density (1.873 g/cm 3 ) respectively are tested using the in situ manganin piezoresistive pressure gauge technique. Numerical modeling of the experiments is performed using an ignition and growth reactive flow model. Reasonable agreement with the experimental results is obtained by increasing the growth term coefficient in the Lee-Tarver ignition and growth model with porosity. Combining the experimental and simulation results shows that the shock sensitivity increases with porosity for PBXC03 having the same explosive initial grain sizes for the pressures (about 3.1 GPa) applied in the experiments.